Religion and Moral Injury in American Vietnam War Films - Brewer, Mary F. (The journal of religion and film, 2021)
This essay focuses on the representation of religion in Stanley Kubrick’s Full Metal Jacket (1987), Oliver Stone’s Born on the Fourth of July (1989), and Brian de Palma’s Casualties of War (1989). It explores how religion intersects with the experience of moral trauma at an individual level, and how the films portray moral injury to be as damaging an aspect of war trauma for Vietnam veterans as grievous physical harm. Further, the essay considers how moral injury is a fundamental component of the collective trauma the nation experienced and, in turn, the culture wars that erupted during and after the war in Vietnam.